2022
DOI: 10.1002/trc2.12308
|View full text |Cite
|
Sign up to set email alerts
|

APOE ε4 and exercise interact in a sex‐specific manner to modulate dementia risk factors

Abstract: Introduction: Apolipoprotein E (APOE) ε4 is the strongest genetic risk factor for Alzheimer's disease and related dementias (ADRDs), affecting many different pathways that lead to cognitive decline. Exercise is one of the most widely proposed prevention and intervention strategies to mitigate risk and symptomology of ADRDs. Importantly, exercise and APOE ε4 affect similar processes in the body and brain. While both APOE ε4 and exercise have been studied extensively, their interactive effects are not well under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 74 publications
(148 reference statements)
0
2
0
Order By: Relevance
“…Therefore, the two optimal exposures may jointly interact with dementia related genetic risk. Emerging evidence confirmed that a higher frequency of participation in physical activity can improve handgrip strength and increase vitamin D level, and the interaction between physical and APOE genotype have been reported [ 44 , 45 ]. Brain structural alteration may be another potential mechanism.…”
Section: Discussionmentioning
confidence: 93%
“…Therefore, the two optimal exposures may jointly interact with dementia related genetic risk. Emerging evidence confirmed that a higher frequency of participation in physical activity can improve handgrip strength and increase vitamin D level, and the interaction between physical and APOE genotype have been reported [ 44 , 45 ]. Brain structural alteration may be another potential mechanism.…”
Section: Discussionmentioning
confidence: 93%
“…The lack of concordance between astroglial-plaque interactions and measures of AD-related pathology suggest the possibility of inherent sex and APOE genotype effects. Indeed, there are numerous observations of sex × APOE interactions across multiple domains in the absence of significant Ab pathology in rodents and humans [32][33][34][35][36].…”
Section: Discussionmentioning
confidence: 99%